Coconut water-based extender for seminal preservation in small ruminants: A meta-analysis study - Reis, Rogério Amorim dos; Torres, Rodrigo de Nazaré Santos [UNESP]; Ribeiro, Iara Magalhães; Torres, Ciro Alexandre Alves; Freitas, Bruna Waddington de (Elsevier, 2023)
Semen extenders based on egg yolk and milk have been widely used in seminal preservation. However, they present health risks due to the transmission of pathogens. Therefore, new studies have emerged seeking for a diluent of vegetable origin, capable of guaranteeing sperm quality and eliminating the risk of contamination. In light of the above, a meta-analytical review was conducted to determine the effect of coconut water as a seminal extender for small ruminants’ sperm preservation. According to the selection criteria, 88 independent comparisons were obtained from the studies included in the meta-analysis. The weighted mean difference (WMD) between treatments with coconut water (diluents including coconut water) and control treatments (diluents without the addition of coconut water) was evaluated using the random-effects model of meta-analysis. Heterogeneity was explored by meta-regression and subgroup analysis, performed using as covariate: type of coconut water, types of control treatment to which coconut water was contrasted, type of preservation, preservation time and animal species. The overall results showed coconut water elicited a positive effect on total motility of sperm cells from cooled semen (P < 0.05), while for the fresh and cryopreserved semen no significant effect was observed. In addition, coconut water showed a positive effect on membrane integrity of sperm cells from fresh semen (P < 0.05). On the other hand, for cooled semen, a negative result was found (P < 0.05). Therefore, the use of coconut water as a seminal extender proved to be a viable alternative for seminal preservation in small ruminants.
Keywords: Coconut water; Cryopreservation; Extender; Sperm; Sperm quality